Subtle effects of radiation on embryo development of the 3-spined stickleback. (June 2020) - Lerebours, Adélaïde; Robson, Samuel; Sharpe, Colin; Smith, Jim T.
Abstract: The Chernobyl and Fukushima nuclear power plant (NPP) accidents that occurred in 1986 and 2011 respectively have led to many years of chronic radiation exposure of wildlife. However, controversies remain on the dose threshold above which an impact on animal health occurs. Fish have been highly exposed immediately after both accidents in freshwater systems around Chernobyl and in freshwater and marine systems around Fukushima. The dose levels decreased during the years after the accidents, however, little is known about the effects of environmental low doses of radiation on fish health. The present laboratory study assesses the effects of an environmentally relevant dose range of radiation (0.1, 1 and 10 mGy/day) on early life stages of the 3-spined stickleback, Gasterosteus aculeatus . The cardiac physiology and developmental features (head width, diameter, area) of high exposed embryos (10 mGy/day) showed no significant change when compared to controls. Embryos exposed to the medium and high dose were slower to hatch than the controls (between 166 and 195 h post-fertilization). After 10 days of exposure (at 240 h post-fertilization), larvae exposed to the high dose displayed comparable growth to controls. High-throughput sequence analysis of transcriptional changes at this time point revealed no significant changes in gene regulation compared to controls regardless of exposure conditions. Our results suggest that exposure of fish embryos to environmental radiation elicits subtle delays in hatching times, but does not impair the overall growth and physiology, nor the gene expression patterns in the recently hatched larvae. Highlights: An environmental dose of radiation of 10 mGy/day do not alter the cardiac physiology and development of fish embryos. Embryos exposed to 1 and 10 mGy/day were slower to hatch than the controls. Larvae exposed to the high dose displayed comparable growth to controls. No significant changes in gene regulation compared to controls regardless of exposure conditions was noticed in larvae.